(untitled) (Research, Society and Development, 2020)
The introduction of conserved forage into the animal diet is a viable and highly relevant strategy, not only in periods of forage shortages by grazing, but also in production systems where the herd is confined, and the food base depends on preserved foods, which participate in significant levels in the composition of the diet. However, a series of circumstances such as climatic conditions, lack of equipment and failure in forage planning, can become a complicating factor for silage production to occur efficiently, ensuring the quantity and quality demanded on the property. And in this context, there is the practice of relocating silage or re-ensiling, which is a growing option in Brazil, aiming to meet the demands mentioned above, such as strengthening the market focused on the sale of silage between farms. Thus, the objective of this work was to carry out a literature review to address the aspects inherent to the reallocation of silage within the rural property. The methodology used is qualitative and descriptive. The research results point to a possible impact on the quality of reallocated silages, however some may exist due to the exposure and possible deterioration of the silage, influencing animal consumption. Studies have shown that this is a practice that can be carried out, however efficiency throughout the entire process will be closely linked to the quality of the final product that will be offered to the animals.